2012
DOI: 10.4317/medoral.17864
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic third molar in the mandibular condyle: A review of the literature

Abstract: Objectives: To evaluate the etiopathogenesis, clinical features, therapeutic options, and surgical approaches for removal of ectopic third molars in the mandibular condyle. Study design: MEDLINE search of articles published on ectopic third molars in the mandibular condyle from 1980 to 2011. 14 well-documented clinical cases from the literature were evaluated together with a new clinical case provided by the authors, representing a sample of 15 patients. Results: We found a mean age at diagnosis of 48.6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 12 publications
(30 reference statements)
4
66
1
5
Order By: Relevance
“…Ectopic teeth are those that are impacted in unusual positions or that have been displaced and are at a distance from their normal anatomic location (Iglesias-Martin et al, 2012;Lambade et al, 2013) and have been reported in the mandibular condyle, coronoid process, orbit, palate, nasal cavity, floor of mouth, and maxillary sinüs (Buyukkurt et al, 2010;Pace et al, 2010;Shivashankara et al, 2012;Lambade et al, 2013). The etiology of an ectopic tooth has not yet been completely clarified.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ectopic teeth are those that are impacted in unusual positions or that have been displaced and are at a distance from their normal anatomic location (Iglesias-Martin et al, 2012;Lambade et al, 2013) and have been reported in the mandibular condyle, coronoid process, orbit, palate, nasal cavity, floor of mouth, and maxillary sinüs (Buyukkurt et al, 2010;Pace et al, 2010;Shivashankara et al, 2012;Lambade et al, 2013). The etiology of an ectopic tooth has not yet been completely clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of an ectopic tooth has not yet been completely clarified. However, an ectopic eruption may result due to either developmental disturbances, iatrogenic activity, or pathological process such as dentigerous cysts (Pace et al, 2010;Buyukkurt et al, 2010;Shivashankara et al, 2012;Iglesias-Martin et al, 2012). Dentigerous cysts are the second most common odontogenic cysts after radicular cysts, accounting for approximately 24 % of all true cysts of the jaw and are the most common developmental cyst of the jaw (Kocer et al, 2002;McCrea, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations